Extracellular Vesicle-Educated Macrophages Promote Early Achilles Tendon Healing. (22nd February 2019) - Chamberlain, Connie S.; Clements, Anna E. B.; Kink, John A.; Choi, Ugeun; Baer, Geoffrey S.; Halanski, Matthew A.; Hematti, Peiman; Vanderby, Ray
Abstract : Tendon healing follows a complex series of coordinated events, which ultimately produces a mechanically inferior tissue more scar-like than native tendon. More regenerative healing occurs when anti-inflammatory M2 macrophages play a more dominant role. Mesenchymal stromal/stem cells (MSCs) are able to polarize macrophages to an M2 immunophenotype via paracrine mechanisms. We previously reported that coculture of CD14+ macrophages (MQs) with MSCs resulted in a unique M2-like macrophage. More recently, we generated M2-like macrophages using only extracellular vesicles (EVs) isolated from MSCs creating "EV-educated macrophages" (also called exosome-educated macrophages [EEMs]), thereby foregoing direct use of MSCs. For the current study, we hypothesized that cell therapy with EEMs would improve in vivo tendon healing by modulating tissue inflammation and endogenous macrophage immunophenotypes. We evaluated effects of EEMs using a mouse Achilles tendon rupture model and compared results to normal tendon healing (without any biologic intervention), MSCs, MQs, or EVs. We found that exogenous administration of EEMs directly into the wound promoted a healing response that was significantly more functional and more regenerative. Injured tendons treated with exogenous EEMs exhibited (a) improved mechanical properties, (b) reduced inflammation, and (c) earlier angiogenesis. Treatment with MSC-derived EVs alone were less effective functionally but stimulated a biological response as evidenced by an increased number of endothelial cells and decreased M1/M2 ratio. Because of their regenerative and immunomodulatory effects, EEM treament could provide a novel strategy to promote wound healing in this and various other musculoskeletal injuries or pathologies where inflammation and inadequate healing is problematic. Stem Cells   2019;37:652–662 : Abstract : Extracellular vesicles (EVs) were isolated from bone marrow derived mesenchymal stem/stromal cells (BMMSCs) via ultracentrifugation. CD14+ monocytes were obtained from peripheral blood, cultured, activated to CD14+ macrophages, and educated with MSC-derived EVs, producing EV-educated macrophages (EEMs). Treatment with EEMs using a mouse Achilles tendon injury model accelerated healing as indicated by reduced inflammation, early angiogenesis, and improved strength and modulus.